(untitled) (Research, Society and Development, 2021)
This work aims to bring data on the study of sarcopenic disease, obesity and sarcopenic obesity. This study aims to assess the presence of sarcopenia in overweight or obese adult individuals. This is a cross-sectional analytical study with a quantitative approach in 100 adult individuals (50 obese and 50 overweight), between 18 and 60 years of age. The studies were carried out in a private clinic in the city of Vitória da Conquista – BA. However, at the end of the application of the questionnaires and collecting data from the individuals, they were tabulated and received descriptive and analytical statistical treatment. The sample showed a predominance of females both in overweight and obese, with no statistically significant difference between groups for gender. Even with the limitations of the research, it was possible to achieve the objectives and bring concrete results that young individuals with a pattern of overweight or obesity can and do have sarcopenia. Further studies are suggested in order to address more scientific evidence in obese and overweight individuals with sarcopenia.